Vernacular Cyber-Sufism: Digital Ritual, Mediated Authority, and the Naqshbandi Haqqani Order in Indonesia - Wahyudi, M. Agus; Srimulyani, Eka; Shadiqin, Sehat Ihsan; Gumilang, Randi Muhammad (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2025)
The article analyzes the incorporation of digital media within the Naqshbandi Haqqani Order in Indonesia and argues that it represents a significant transformation in contemporary Sufi practice. Based on qualitative interviews with members of local zāwiyahs, the study shows that digital platforms facilitate core tariqa practices, including online bay’a, virtual dhikr, and digital sahba. These practices demonstrate that digital space functions not merely as a medium of communication but as a legitimate site of ritual performance and spiritual experience. The findings challenge the conventional distinction between “religion online” and “online religion” by illustrating how barakah and spiritual authorization are reconfigured through technological mediation. The article contributes theoretically by introducing the concept of vernacular cyber-Sufism, in which local zāwiyahs act as espitemic intermediaries translating transnational Sufi authority into locally meaningful forms. This process reflects a pattern of negotiated authority shaped by the interaction of global charisma, local mediation, and platform visibility. At the same time, digital expansion produces ambivalent effects, simultaneously widening access to Sufi learning while raising concerns about authenticity and the commodification of knowledge.